Família é aquilo que falta: repercussões da separação conjugal dos pais na trajetória de universitários amazônidas - Souza, Sander Firmo de (Brasil, 2024)
The present work addresses marital separation and divorce of parents of young Amazonians, aiming to understand the repercussions of separation on the trajectory of university students from municipalities in the interior of Amazonas. Starting from the identification of the main psychosocial approaches to marital separation, divorce and family transformations, qualitative research in an exploratory nature was carried out, which included a Scoping Review on Family in the Amazon region and interviews with 3 participants, using the Narrative Interview and semi-structured interview as tools. 14 productions were identified that pointed to structures, gender roles and dynamics and transformations in families in municipalities in the interior of Amazonas, with variations in the nuclear family model, especially due to the presence of grandmothers. The interviewees showed the plurality of family arrangements that occur after marital separations, like a unique “sewing” or “embroidery”, yet, involving common themes. They also reveal the ways of life in the Amazon interior and the transition between rural and urban spaces, and the difficulties of concrete ways of producing life. The gender roles of parents seem to play a determining role in the continuity of their children's schooling. Aspects related to gender roles, structure, socioeconomic reality and idealization of the family based on abstract and ideological models emerged as elements that tension aspects related to cultural identity, family ties and future projects.